The Effect of Service Quality Prices and Location of Companies to Customer Satisfaction Implications on Customer Loyalty - Henny Risnawati; Hendi Eka Sumarga; Sugeng Purwanto (International Review of Management and Marketing, 2019)
The purpose of this study was to determine the effect of service quality, price suitability, company location, and customer satisfaction partially or jointly on customer loyalty in freight forwarders in Jabodetabek. The research method used in this research is descriptive and explanatory survey methods with a sample size of 270 respondents and the data analysis method used is SEM (Structural Equation Modeling) with a lisrel 8.80 data analysis tool. Based on the results of the study, the following findings were obtained: service quality, price suitability, and company location partially or jointly had a significant effect on customer satisfaction with a contribution of 62%. Partially the quality of service has the most dominant influence on customer satisfaction. Service quality, price suitability, company location, and customer satisfaction partially or jointly have a significant effect on customer loyalty with a contribution of 85%. Partially customer satisfaction is most dominant in influencing customer loyalty. The results also show that customer loyalty is a full mediating variable on the effect of service quality, price suitability, and company location on customer loyalty. The results of this study provide managerial implications for freight forwarders that to increase customer loyalty reflected in the dimensions of showing immunity to competitors is to increase customer satisfaction which is reflected by an increase in the dimension of price perception, where customer satisfaction will increase if freight forwarders are able to improve service quality, especially reflected in the assurance dimension, which is supported by increasing price conformity, especially reflected in increasing dimensions of product price conformity with the benefits obtained and supported also by increasing the ease of company location, especially as reflected in an increase in the visibility dimension.